Analisa Pemakaian Alat Kesehatan pada Rumah Sakit Menggunakan Analytical Hierarchy Process (AHP) - Hafis Nurdin; Irwan Agus Sobari; Aji Sudibyo; Bambang Wijonarko; Felix Wuryo Handono; Taufik Asra (PT FORMOSA CENDEKIA GLOBAL, 2022)
Medical devices are items that are needed in the medical world. Because too many types of medical devices are used, a comparison was made to choose medical devices that are often used in hospitals, especially by operating room (OT) nurses. So a research was made using the Analytical Hierarchy Process (AHP) method. AHP is an alternative for making decisions that have several goals or criteria. To complete the input, it is assisted by the Expert Choice 11 application. From the results of data processing, it is concluded that for the use of medical devices that are often used in hospitals, there are several influencing factors, namely packaging, quality, usage and indications. While the medical devices that are often used are Pencil Couter, Grounding Plate, Syringe and Gloves.